Between Modernization and Capitalization: Commercialization of Malang in The Early Twentieth Century (History Department, Semarang State University and Historian Society of Indonesia, 2021)
Abstract: Colonialism, capitalism, and the city are three elements that always correlated. At the beginning of the 20th-century cities, growth was inseparable from the economic expansion of Dutch capitalism represented by the plantation industry, trade offices, insurance offices, and elite shopping areas. The exploitation of urban space followed this process. As the regime changed in early 1942, the growth of the symbol of capitalism in the city was halted by the Japanese Military Government. This article attempts to explain the relationship between the development of capitalism, the modernization of the city, and its impact on society. To explain this connection, the author uses historical methods using the city government report. Based on analysis of municipal tax report and the response of indigenous people who lived within the city, it can be concluded that there is an influence of capitalism on the high intensity of exploitation and conflict in struggling for urban space. Modernization of the city is not merely efforts to create a city comfortable and hygienic, but the strategy of commerce urban space. Modernization of the colonial city has covered the suffering of most people that have their own way of living. Abstrak: Kolonialisme, kapitalisme dan kota adalah tiga unsur yang selalu berkorelasi. Pada awal abad ke-20 pertumbuhan kota tidak terlepas dari ekspansi ekonomi kapitalisme Belanda yang diwakili oleh industri perkebunan, perkantoran perdagangan, perkantoran asuransi dan kawasan perbelanjaan elit. Proses ini diikuti dengan eksploitasi ruang kota. Ketika rezim berganti pada awal 1942, pertumbuhan simbol kapitalisme di kota itu dihentikan oleh Pemerintah Militer Jepang. Artikel ini mencoba menjelaskan hubungan antara perkembangan kapitalisme, modernisasi kota dan pengaruhnya terhadap masyarakat. Untuk menjelaskan hubungan tersebut, penulis menggunakan metode sejarah dengan menggunakan laporan pemerintah kota. Berdasarkan analisis laporan pajak kota dan respon masyarakat adat yang tinggal bersama di kota dapat disimpulkan bahwa terdapat pengaruh kapitalisme terhadap tingginya intensitas eksploitasi dan konflik dalam memperebutkan ruang kota. Modernisasi kota bukan semata-mata upaya menciptakan kota yang nyaman dan bersih, tetapi strategi perdagangan ruang kota. Modernisasi kota kolonial telah menutupi penderitaan sebagian besar masyarakat yang memiliki cara hidup sendiri-sendiri.